Nurses’ opinion on an instrument of systematized medical care for the emergency patient - Candice Abdon Miranda; Elisabeth do Nascimento Silveira; Raquell Alves de Araújo; Bertha Cruz Enders (Rev Rene, 2012)
This exploratory study aimed at identifying nurses´ opinions on an instrument of care, based on the Systematization of Nursing Assistance to be used in the emergency room. It was carried out in a large hospital in Recife, Pernambuco, Brazil, from June to August 2009, with an accidental sample of 30 emergency nurses. The data were collected by means of a questionnaire and analyzed using descriptive statistics. Most nurses had a favorable opinion of the instrument´s contribution to the: work in the emergency room (96,6%); quality of nursing care (86,6%); action planning (97,0%); nurse´s autonomy (86,9%); and the communication and integration of the multi-professional team (83,6%). Besides that the nurses say that to use the form is viable (80, 0%). Suggestions for improvement were organizational in nature and for the addition of content.